(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
Modelling responses of groundwater levels in aquifer systems, which occur as a reaction to changes in aquifer system boundary conditions such as river or stream stages, is commonly being studied using statistical methods, namely correlation, cross-correlation and regression methods. Although correlation and regression analysis tools are readily available in Microsoft Excel, a widely applied spreadsheet industry standard, the cross-correlation analysis tool is missing. As a part of research of groundwater pressure propagation into alluvial aquifer systems of the Sava and Drava/Danube River catchments following river stages rise, focused on estimating groundwater pressure travel times in aquifers, an Excel spreadsheet data analysis application for cross-correlation modelling has been designed and used in modelling surface water – groundwater interaction. Examples of fi eld data from the Zagreb aquifer system and the Kopački rit Nature Park aquifer system are used to illustrate the usefulness of the cross-correlation application.